Phonics Instruction with Storytelling Toward Learning to Read and Oral Language Development - Ahmad Syarif; Yetti Supriyati; Zulela Zulela (TARBIYA: Journal of Education in Muslim Society, 2019)
AbstractThis study aims to examine the influence of phonics instruction with storytelling toward the students’ learning to read and the influence of phonics instruction with storytelling toward the students’ oral language development at first grade in elementary school. The subject of research is the first students at class A and class B at SDN Siliwangi that located in Bogor. The approach of this research is quantitative and the method used quasi-experiment. The design of this research used Nonequivalent Groups Postest-Pascatest with a purposive sample technique. The total samples were 60 students of first grade in SDN Siliwangi that are divided into two classes. The class control is 30 students, and the experiment class is 30 students. The data were collected through the test, namely test for measuring learning to read and test for measuring oral language development. The result of research finds out that phonics instruction with storytelling was better than conventional learning toward students' learning to read and oral language development. The novelty of this research shows that students pronounced the simple text easier, fluency, and communicative when they described their idea orally after given phonics instruction with storytelling. The second novelty of this result found that phonics instruction was effective when the teacher at elementary school facilitates students' level from the beginning until the advanced level.  The teacher should be implemented this instruction for helping students’ low achievement, especially for improving students’ oral language development. Finally, this result should be developed so that it more perfect and more practice.AbstrakStudi ini bertujuan untuk menguji pengaruh instruksi fonik dengan mendongeng terhadap pembelajaran membaca siswa dan pengaruh instruksi fonik dengan mendongeng terhadap perkembangan bahasa lisan siswa di kelas satu di sekolah dasar.. Subjek penelitian adalah siswa pertama di kelas A dan kelas B di SDN Siliwangi yang berlokasi di Bogor. Pendekatan penelitian ini adalah kuantitatif dan metode yang digunakan eksperimen semu. Desain penelitian ini menggunakan Nonequivalent Groups Postest-Pascatest dengan teknik sampel purposive. Total sampel adalah 60 siswa kelas I di SDN Siliwangi yang dibagi menjadi dua kelas. Kontrol kelas adalah 30 siswa dan kelas eksperimen adalah 30 siswa. Data dikumpulkan melalui tes, yaitu tes untuk mengukur pembelajaran membaca dan tes untuk mengukur perkembangan bahasa lisan. Hasil penelitian menemukan bahwa pengajaran fonik dengan mendongeng lebih baik daripada pembelajaran konvensional terhadap pembelajaran membaca dan pengembangan bahasa lisan siswa. Kebaruan dari penelitian ini menunjukkan bahwa siswa mengucapkan teks sederhana lebih mudah, lancar, dan komunikatif ketika mereka menggambarkan ide mereka secara lisan setelah diberi instruksi fonik dengan mendongeng. Kebaruan kedua dari hasil ini menemukan bahwa pengajaran fonik efektif ketika guru di sekolah dasar memfasilitasi tingkat siswa dari awal hingga tingkat lanjutan. Guru harus mengimplementasikan instruksi ini untuk membantu siswa berprestasi rendah, terutama untuk meningkatkan pengembangan bahasa lisan siswa. Akhirnya, hasil ini harus dikembangkan sehingga lebih sempurna dan lebih banyak latihan.How to Cite: Syarif, A. Supriyati, Y., Zulela. (2019).   Phonics Instruction with Storytelling Toward Learning tTo Read and Oral Language Development. TARBIYA: Journal of Education in Muslim Society, 6(2), 210-219. doi:10.15408/tjems.v6i2. 14322.